PENGARUH MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA KELAS X PROGRAM KEAHLIAN TATA KECANTIKAN RAMBUT DI SMKN 7 PADANG - indah utami sri wahyuni (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This research is motivated by the learning process. Quantitative research methods with correlational research types.The population is 58 students,technique uses total sampling. Quantitative analysis techniques. The results showed the level of use of instructional media by class X students of hairstyling at Padang State Vocational High School amounted to 75.81% good category which was viewed from visual media indicators as much as 73.95% good category and audio visual media by 75.81% good category. The level of student motivation is 78.74% in the good category which is viewed from the indicators of desire and desire of success of 79.23% in the good category, the encouragement and learning needs of 78.16% in the good category, the hopes and aspirations of the future amount to 78.10% good category, the award in learning amounted to 77.70% in the good category, the presence of interesting desires in learning by 50.23% in the fairly good category and the existence of a conducive learning environment of 82.41% in the very good category. The results of the analysis and hypothesis testing have a significant effect with a low level of influence of 6.9%.